PFM.42 Maternal hypomagnesaemia leading to fetal ventricular ectopics. (9th June 2014) - O'Flynn, H; Patankar, S; Noor, C; Rice, C
Abstract : Background: Fetal arrhythmias occur in 1–2% of pregnancies, but associated morbidity and mortality is reported in 10% 1 . Intravenous magnesium administered in the post natal period is a recognised treatment of fetal ventricular tachycardia 2 . We present a case of fetal ectopic beats resolved by correction of abnormal maternal magnesium levels. Case: A 32 years old primip at 41 weeks gestation, presented with palpitations. She was of African origin and was treated for malaria in the past. ECG had non specific ST and T wave changes. Maternal hypomagnesaemia - 0.67[0.7–1.0 mmol/litre] was demonstrated. The cardioctocograph [CTG] showed irregular fetal tachycardia with ectopic beats and decelerations to 60bpm, confirmed on ultrasound. She was given 1 gram of magnesium sulphate intravenously. Repeat magnesium levels were normal- 0.9mmol/l. Following magnesium administration maternal and fetal tachycardia resolved. Induction of labour was commenced and subsequently Caesarean section was performed for pathological CTG. Baby had a regular heart rate and no intervention was required. Discussion: First degree atrioventricular block has been demonstrated in 2.6% of cases of isolated ectopy. Second degree AV block and prolonged QT syndrome are also described 3, 4 . Little has been reported in the literature on the effect of maternal hypomagnesaemia on fetal arrhythmias. Two cases were identified which used administration of magnesium in the antenatal period to control fetal ventricular tachycardia 2, 5 . However in these cases maternal serum magnesium was within the normal range. Conclusion: We propose that maternal hypomagnesaemia is a potential cause of irregular fetal ectopic beats. Further research should be done to confirm this observation and recommend treatment.